A data labelling technique for high-performance protocol processing and its consequences. - Feldmeier, David C. (Computer communication review.)
Reordering and reassembly of data before processing can reduce communication system performance as seen by the application. We examine a method of explicitly labelling blocks of data with sufficient information to allow processing of misordered data. Our labelling syntax for data blocks, which we call chunks, is cleaner and more general than that of other protocols. We show how chunks can be used for efficient fragmentation/reassembly and compare chunks with other fragmentation systems. End-to-end error detection is complex for chunks or other systems that allow both fragmentation and processing of misordered data. We show that it is possible to design an end-to-end error detection system that does not compromise chunk processing performance. Chunks can take advantage of processing techniques such as Integrated Layer Processing and can be used to implement concepts such as Application Layer Framing [CLAR 90].